PENINGKATAN HASIL BELAJAR MENGELOLA DANA KAS KECIL MELALUI MODEL PEMBELAJARAN THINK PAIR AND SHARE SISWA KELAS XI AP2 SMK NEGERI 1 LUMAJANG - Kusdariyanto - (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2015)
It is generally difficult for students to understand the subject of managing petty cash fund, especially to understand the materials of bookkeeping patty cash fund. As a teacher, the writer has a very strong will to encourage students to get tremendous learning achievement, at least as the same score as the criterionof minimumcompleteness (KKM). This study is aimed at improving the students’ achievement in managing petty cash fund through the implementation of think, pair, and share strategy at grade XI office administration programs (AP2) of SMK Negeri 1 Lumajang. The findings show that the development of the students’ score has significantly increased, approximately 34,29%. On the basis of research findings, it can be concluded that think, pair, and share strategy can develop their skills in managing petty cash fund.Keywords: petty cash fund, think pair and share strategy, students’ achievement.